Stereodivergent Metal-Catalyzed Allene Cycloisomerizations - Reeves, Ryan D.; Kinkema, Caitlin N.; Landwehr, Eleanor M.; Vine, Logan E.; Schomaker, Jennifer M. (Synlett, 2020)
Metal-catalyzed allene cycloisomerizations provide rapid entry into five-membered carbocyclic frameworks, a common motif in natural products and pharmaceuticals. While both Au(I) and Pd(0)-catalyzed allene cycloisomerizations give 5-endo-dig cyclization, Pd prefers the syn diastereomer in contrast to the anti isomer observed with Au. The change in stereoselectivity is proposed to arise from buildup of A1,3 strain during the key carbopalladation step to furnish the cycloisomerized products in moderate to good dr with yields comparable to Au(I) catalysts.
Keywords: allene; cycloisomerization; cyclopentene; Conia-ene; carbopalladation; carbocycle